PEMANFAATAN LAHAN PEKARANGAN DALAM MENINGKATKAN PENDAPATAN KELUARGA DI KECAMATAN ASERA KABUPATEN KONAWE UTARA - Rostin, Rostin; Putera, Asrip; Anto, Rola Pola; Yunila, Yunila; Dewi, Made Listia; Rahayu, Sara Evi (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
One of the strategies of the North Konawe Regency Regional Government in encouraging the use of existing resources in order to increase community income is to maximize the function of yard land which has been "idle land" or has not been managed properly. In general, the area of house yards in North Konawe Regency, including in Asera District, is relatively large so that it can be managed to support family income. A creative mindset and culture is needed in utilizing yard land, such as cultivating horticultural plants, which can contribute to meeting daily food needs so as to reduce the cost of daily shopping for family needs. In this case, the activities are focused on yard land resources, where yard land is land whose function has not been optimized. The method for implementing community service activities in Asera District, North Konawe Regency will be carried out in two stages, namely the preparation stage and the implementation stage. The preparation stage is preparing the needs for training activities for the community (1) Arranging permits from the Village Government in Asera District, (2) Preparing equipment for carrying out counseling. (3) Create and send invitation letters to the target communities for the training. Implementation of service activities in Asera District, North Konawe Regency includes the following activities: (1) Activities explaining the benefits of managing homestead land to support family income. (2) The activity explains how to use yard land to support family income. (3) Providing encouragement to the community, especially housewives, to use their yard as an alternative source of family income. The target of this training is the community , especially housewives in Asera District , North Konawe Regency. To find out the success of the training that has been carried out, direct responses are asked from the participants regarding matters relating to the training material. From these answers, it can be seen whether the participants can understand and understand the training material well, so that housewives' interest in using the yard land increases or increases in the future. Activity Results; (1) Longeo Utama Village, Asera District , North Konawe Regency has quite a large yard area in every resident's house (2) The majority of people and housewives have not used yard land as an additional source of family income. (3) The majority of people and housewives have the enthusiasm and desire to progress , but have limitations in terms of experience and knowledge in utilizing yard land as a family opinion, so that the majority of people's yard land appears to be underutilized